Novel algorithm for dynamic bandwidth scheduling in WDM EPON - Xue-shun WANG; Shao-hua YU; Jin-you DAI (Tongxin xuebao)
Optical network unit(ONU)grant scheduling techniques for wavelength division multiplexed Ethernet passive optical networks (WDM EPON) was investigated and the grant scheduling problem based on scheduling theory was solved the question was formulated into a rectangle packing problem and a high performance ONU grant scheduling policy based on Euclidian distance was proposed by taking quasi-human strategy.An effective heuristic algorithm was provided to quickly solve ONU grant scheduling problem in WDM EPON.Further simulation experiments show the grant scheduling algorithm can decrease average packet delay and increase network utilization.The results indicate the effectiveness of this algorithm.